TINJAUAN PSIKOLOGI KESEHATAN PADA PENDERITA PENYAKIT KAKI GAJAH KRONIS DI KABUPATEN BANDUNG - Ambar Sulianti (Psympathic : Jurnal Ilmiah Psikologi, 2014)
Elephantiasis or Filariasis has been reported endemic in Kabupaten Bandung with potentially result in defects. This research aimed to explore health psychology of chronic Elephantiasis patients in Kabupaten Bandung. Qualitative-descriptive method has been used to explore the respondent’s psychodynamics, health behavior, and treatment seeking behavior, while quantitative-descriptive method has been used to determine the percentage distribution. The result showed that there were three kind of respondent’s psychodynamic namely denial (7.7%), anxiety (85%), and depression (7.7%). Due to the lack of knowledge about the disease, the majority of respondents (77%) were hiding their disease.Type of treatment seeking behaviors has been chosen by respondent namely relying to the paranormal (92%), doctors (23%), traditional physician (54%), and acupuncturist (15%).